Comprehensive Raman study of orthorhombic κ/ε-Ga2O3 and the impact of rotational domains. Issue 40 (29th September 2021) - Janzen, Benjamin M.; Mazzolini, Piero; Gillen, Roland; Peltason, Vivien F. S.; Grote, Linus P.; Maultzsch, Janina; Fornari, Roberto; Bierwagen, Oliver; Wagner, Markus R.
Abstract : The Raman-active phonon modes of orthorhombic gallium oxide (κ/ε-Ga2 O3 ) are investigated by combination of polarized micro-Raman spectroscopy and density functional perturbation theory (DFPT) calculations. Abstract : Gallium oxide (Ga2 O3 ) is an ultra-wide bandgap material, which has recently attracted widespread attention for holding promising applications in power electronics and solar blind UV photodetectors, outclassing GaN or SiC in terms of a larger bandgap and higher breakdown voltages. The orthorhombic κ phase (also referred to as ε) has sparked particular interest for offering higher symmetry than β, while featuring ferroelectric behavior paired with a large predicted spontaneous polarization, paving the way to fabricating high-quality two-dimensional electron gases for application in heterostructure field effect transistors. The presently available κ phase samples are characterized by a domain structure, in which orthorhombic domains are rotated 120° against each other within the c -plane forming a pseudo-hexagonal structure, which has previously often been ascribed to ε-Ga2 O3 and incorrectly been viewed as this polymorph's true crystal structure. A detailed investigation into the phonon modes of orthorhombic κ-Ga2 O3 provides insights into fundamental material properties such as crystal structure and orientation as well as the vibrational symmetries of Raman active modes. We investigate the Raman active phonon modes of an MBE-grown orthorhombic κ-Ga2 O3 thin film featuring the domain structure deposited on (0001)-Al2 O3 by experiment and theory: Polarized micro-Raman spectroscopy measurements in conjunction with density functional perturbation theory (DFPT) calculations enable the identification of both the frequencies and vibrational symmetries of the Raman active phonons. Presenting comprehensive Raman spectra of the orthorhombic κ phase, the experimental frequencies of more than 90 Raman modes are determined and correlated with the 117 modes predicted by the calculations. Angular-resolved Raman measurements are utilized to provide an experimental verification of phonon mode symmetries. We present an analytical tool to deal with the domain structure and its effect on the obtained Raman spectra.